2015
DOI: 10.1155/2015/213635
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thickness of Aluminium Films on Optical Reflectance

Abstract: In Uganda and Africa at large, up to 90% of the total energy used for food preparation and water pasteurization is from fossil fuels particularly firewood and kerosene which pollute the environment, yet there is abundant solar energy throughout the year, which could also be used. Uganda is abundantly rich in clay minerals such as ball clay, kaolin, feldspar, and quartz from which ceramic substrates were developed. Aluminium films of different thicknesses were deposited on different substrates in the diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…To show this more clearly, in Figure 14d the reflectance values of each sphere type at a wavelength of 15 µm is plotted against the layer thickness. A similar behavior was observed by Lugolole et al [20]. Interestingly, a similar layer thicknesses of approx.…”
Section: Lpd-coated Spheres -Setupsupporting
confidence: 89%
See 2 more Smart Citations
“…To show this more clearly, in Figure 14d the reflectance values of each sphere type at a wavelength of 15 µm is plotted against the layer thickness. A similar behavior was observed by Lugolole et al [20]. Interestingly, a similar layer thicknesses of approx.…”
Section: Lpd-coated Spheres -Setupsupporting
confidence: 89%
“…Despite the coated layer, for both types of spheres, no or less reflectance increase can be observed. This behavior was already established by Lugolole et al [20], where the lowest reflectance was achieved with the sample, which has a rough surface. Das et al [28], Moushumy et al [29], and Sharma et al [30] also show numerical simulations of different nano-structured gratings on GaAs substrates, that the surface structure has a significant influence on the reflection behavior.…”
Section: Lpd-coated Spheres-setupsupporting
confidence: 74%
See 1 more Smart Citation
“…R. Lugolole et al reported that when Al film was deposited on a ceramic substrate, the reflectance increased with increasing film thickness. The maximum reflectance was reached when the thickness was about 750 nm [25].…”
Section: Resultsmentioning
confidence: 99%
“…Aluminum is a typical example proving this phenomenon. The aluminum oxide film is assumed to produce a dull finish on the metal surface, owing to its considerable thickness (~0.5-1 µm) [13,14]. The light scattering on natural oxidized copper is also due to the oxide film, the thickness of which was calculated to be about 627 nm [15].…”
Section: Electropolishing Mechanismsmentioning
confidence: 99%